Decisive years in France, 1840-1847 - Pinkney, David H. (Princeton legacy library., 1986)
David Pinkney challenges accepted views of the timing of France's Industrial Revolution and the accompanying transformation of French society. Originally published in 1986. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich sch.